Antioxidant and phytochemical analysis of leaves from three variety Melastoma Malabathracium - Mohamad Hilmi, Mohamed Nawawi (2015)
Melastoma Malabathracium is a well-known plant and easy to find, especially in Asian region. It is the plant from the family of Melastomataceae. There are a lot of uses for Melastoma Malabathracium reported in old folk such as diarrhoea, cuts and wounds, infection during confinement. The study of this research is to compare antioxidant activity on three varieties of Melastoma Malabathricum which are white and purple flower of Melastoma Malabathracium and wild Melastoma Malabathracium, to determine total phenolic compound of Melastoma Malabathracium from three different Melastoma Malabathracium, and to test the present of antioxidant activity using Thin Layer Chromatography (TLC). For this study, 3 method been use DDPH and TLC to test antioxidant properties in the malestoma malabathracium,. For phenolic content, method used was using total phenolic content (TPC). For DPPH, the control or positive using ascorbic acid to compared with the sample and for TPC using galic acid. Antioxidant test for three verity Melastoma Malabathricum which are melastoma malabathracium with white flower, malestoma malabathracium with purple flower and wild malestoma malabathracium show higher percentage of DDPH. From the test been done malestoma malabathracium with purple flower show the lowest ic₅ₒ which is 2.40±0.12, the lowest ic₅ₒ show the higher antioxidant ability. For total phenolic content white flower show the higher which is 4.55± 1.56, compared to other malestoma.